The 3‐D Facies and Geomechanical Modeling of Land Subsidence in the Chaobai Plain, Beijing. Issue 3 (20th March 2020) - Zhu, Lin; Franceschini, Andrea; Gong, Huili; Ferronato, Massimiliano; Dai, Zhenxue; Ke, Yinghai; Pan, Yun; Li, Xiaojuan; Wang, Rong; Teatini, Pietro
Abstract: The hydrogeologic systems of alluvial fan are characterized by a heterogeneous distribution of various lithological units/facies. The structure (integral scale and volumetric proportion) of the hydrofacies distribution and the values of the hydrogeomechanical parameters of each facies can play a major role on the system response to groundwater withdrawal in term of land subsidence. We propose a novel approach where stochastically simulated hydrofacies distributions are coupled with 3‐D finite element groundwater flow and geomechanical simulations to characterize land subsidence and horizontal movements due to groundwater withdrawal under a statistical framework. The integrated approach is applied on the Chaobai alluvial plain, China, an area of about 1, 100 km 2 where the main wellfields supplying water to Beijing are located. Groundwater pumping from the 1960s to now caused a land subsidence larger than 1 m and the present subsidence rate peaks to 70 mm/year. A Monte Carlo simulation with 100 hydrofacies generations is used. The model outcomes highlight how the heterogeneous structure of the hydrofacies fan reflects into the computed displacement fields. The standard deviation associated to the mean displacement field amounts up to 1/10 of the displacement components. The larger coefficient of variation ( CV up to 0.5) is associated to the zone characterized by longer integral scale and with localized groundwater withdrawals. The computed variability of the subsidence rate, in the range of 1 to 3 mm/year, reflecting the intrinsic heterogeneous nature of an alluvial fan, corresponds to the short‐distance variability of land subsidence measured by persistent scatterer interferometry. Key Points: The 3‐D hydrofacies coupled to 3‐D FE flow and geomechanical models allow characterizing land subsidence from alluvial fans Integral scale of 3‐D hydrofacies and withdrawal features (localized vs. distributed) control the variability of the land movements A first application on the Beijing alluvial fan, with the uncertainty due to facies distribution quantified in 10% of the average subsidence